Degenerative and inflammatory hand joint changes in osteoarthritis according to magnetic resonance imaging - D. M. Kudinsky; A. V. Smirnov; L. I. Alekseeva; A. V. Volkov; E. A. Taskina; А. M. Lila (Научно-практическая ревматология)
Erosive osteoarthritis (EOA) of the hand is an osteoarthritis (OA) phenotype that is characterized by central and marginal erosions of the articular surfaces in the distal and proximal interphalangeal (DIP and PIP) joints and in some cases by a fairly aggressive course with obvious pain syndrome and a high level of functional impairment. Diagnostic criteria and management tactics for EOA patients are still under investigation.Objective: to evaluate the nature of the changes detected by hand joint magnetic resonance imaging (MRI) in patients with EOA and non-erosive OA (NEOA) of the hand.Subjects and methods. Examinations were made in 61 females meeting the American College of Rheumatology (ACR) diagnostic criteria for hand OA; the patients' mean age was 66.34+5.79 years; the median age at disease onset was 50 [45; 56] years; the duration of pain was 15 [11; 20] years. All the patients underwent MRI of the second-fifth DIP, PIP, and metacarpophalangeal (MCP) joints of the right hand. The patients also filled out the AUSCAN questionnaire. EOA and NEOA were detected in 30 and 31 patients, respectively.Results and discussion. The patients with EOA and those with NEOA were matched for gender, age, and disease duration. The DIP joints in patients with EOA were found to have significantly more frequently and a greater number of large osteophytes (OPs), (53 and 16%, respectively), joint space narrowing (JSN) (73 and 35%), degenerative collateral ligament changes (DCLCs) (93 and 55%), subluxations (47 and 13%), and bone marrow edema (BME) (57 and 19%) than in those with NEOA. Synovitides and subchondral cysts occurred with approximately the same frequency in EOA and NEOA. The PIP joints in patients with EOA significantly more frequently showed BME (37%) and DCLCs (97%) than in those with NEOA. Subluxations in the PIP joint of the right hand were encountered exclusively in patients with EOA. Their incidence was 17%. Degenerative symptoms (small, less often moderate sizes of OPs, JSN, and DCLCs) were identified with approximately the same frequency in both groups (p>0.05). The PIP joints in patients with EOA were significantly more often found to have BME (53 and 26%, respectively; (p<0.05), cortical defects (CDs) of the metacarpal head (73 and 45%) than in those with NEOA. The incidence of subchondral cysts, OPs, JSN, and DCLCs was not significantly different in both groups (p>0.05). Large OPs in the PIP joint were found relatively rarely. Subluxations in the PIP joints were undetected in both groups.Conclusion. The symptoms of active inflammation are predominant and degenerative changes are more pronounced in patients with EOA unlike those with NEOA. Articular surface defects in the PIP joints in patients with hand OA differ from erosions in those with rheumatoid arthritis. These CDs in EOA are much more common than those in NEOA; however, the nature of their occurrence is unclear; therefore, the patients in whom they have been found need dynamic monitoring.